Serological Results Of Cases With A Presumptive Diagnosis Of Hydatid Cyst During 1999-2002 In The İnönü University Medical Faculty, Malatya (Annals of Medical Research, 2021)
None
Keywords: Hydatid Cyst, Malatya, IHAT, IFAT